Advancing Grid-Connected Renewable Generation Systems - Elizaveta Liivik; Yongheng Yang; Ariya Sangwongwanich; Frede Blaabjerg (Applied Sciences, 2021)
If we look at the history of renewable energy sources (RESs), how it all began, and how rapidly they continue to develop, it can be argued that one of the main reasons is due to the rapid improvements in power electronics technology in interfacing the renewable source to the grid [...]